(untitled) (La U Investiga, 2021)
The recognition of the risk, of contracting HIV, as the probability of suffering or contracting this disease, leads to a positive transformation of the state of health. An observational, quantitative and educational intervention study was carried out, by stratified random sampling, 146 students from the Technical University of the North, willing to participate and stay in the institution during the research time. The students were between the ages of 17 - 23 years, 55% of the women between 18 - 20 years, also the men, although in less frequency of participants, 28%, 70.8%, referred information about the disease, which that was positively modified in 100.0% of this group. 41% identified unprotected sexual relations as the main risk, and the same percentage obtained information on the subject from their Internet access. It was concluded, with significant variations in the knowledge of university students on the subject.